THE INFLUENCE OF LEADERSHIP AND WORK DISCIPLINE ON EMPLOYEE JOB SATISFACTION - Dwiki Fatur Rizki; Editya Nurdiana; Sandi Nasrudin Wibowo (SEAN Institute, 2023)
This research uses quantitative methods. In collecting data, researchers used interviews, questionnaires, and observation to obtain complete and accurate information and then processed it using SPSS tools. With the number of respondents as many as 65 employees at Cv. Agung Jaya Putra Furniture Cirebon. Based on the results of the research tests that the researchers conducted, that the influence of leadership and work discipline on job satisfaction at Cv. Agung Jaya Putra Furniture Cirebon The results of testing the hypothesis prove that leadership has an effect on job satisfaction. The results of hypothesis testing prove that work discipline has no effect on job satisfaction. And the results of testing the hypothesis prove that leadership and work discipline simultaneously have a positive effect on job satisfaction.